La creación de valor en los sistemas productivos virtuales: Un modelo de análisis - Soriano Pinar, Isabel; García Muiña, Fernando E.; Pelechano Barahona, Eva (Cuadernos de Estudios Empresariales, 2006)
Higher levels of dynamism, complexity, and the technological intensity of present-day environments, as well as the development of information and communication technologies, have provoked the externalization of several organizational processes, what is known as virtualization of operations systems. This phenomenon can be analysed from different strategic management theories. Literature does not offer an integrative definition, classification, and characterization of virtual systems. Therefore, this work focuses on a critical analysis of extant conceptual contributions, to pre- sent a comprehensive view for the definition of the firm virtualization process, including those criteria virtual systems must fulfill. Additionally, we develop the analysis of those variables that explain the virtualization degree organizations may have. From this analysis, we develop a generic typology of them. Finally, we present an explanatory model concerning the strategic relevance of virtual systems in comparison to other more traditional ones.